Group Activity Therapy (Gat) Socialization Session 6 Increase Socialization Ability on Child of Mental Retardation - Ah. Yusuf; Khoridatul Bahiyah; Yustina Barek Ola (Universitas Airlangga, 2008)
Introduction: The main problem that experienced by child of mental retardation was slowness development of socialization ability especially the ability to cooperate. This disability happened because less of stimulation activity and because of the extraordinary school give more lessons to increase intelligence ability. Group Activity Therapy (GAT) Socialization is a therapy given to child of mental retardation to train their cooperate in playing group and increased their socialization ability (cooperate). Method: This study used Quasy Experimental design. The population was the students of 1-5 class at Karya Bhakti extraordinary school. The sample was recruited with purposive sampling consist of 20 respondents according the inclusions criteria and divided into treatment and control groups. The Independent variable was GAT Socialization session 6 and the dependent variable was the increased of socialization ability (cooperate). Data were collected with observation sheet and analyzed with Wilcoxon Signed Rank Test and Mann Whitney U Test with level of significance p<0.05.Result : The result showed that given GAT Socialization could increased the socialization ability (cooperate) with the result of statistical test showed significance level p=0.004, that means there was differences of the socialization ability pre and post test and between treatment and control group, showed the result of statistical test with significance level p 0.031. Discussion: It can be conclude that GAT Socialization could increase socialization ability (cooperate). Recommendation for teachers could give the lessons in one group and not only individual. Important to do for further research until GAT Socialization session 7 for increased socialization ability.